Penentuan MUF Menggunakan Model Sederhana Ionosfer Regional Indonesia - Buldan Muslim (Institut Teknologi Bandung, 2002)
Indonesian simplified ionospheric regional model (ISIRM) is modified of simplified ionospheric regional model (SIRM) which was originally developed for modeling the most relevant ionospheric characteristics over Europe for radiocommunication purposes. The model, based mainly on a Fourier expansion of a reference previous data set, have a good agreement at midlatitude region. This paper describe the modeling of (ISIRM) based on ionospheric data observation at low latitude around Indonesian region: Manila, Singapura, Vanimo, and Darwin, for two of important ionospheric parameter needed for maxmimum usable frequency (MUF) determination i.e: foF2 and M(3000)F2. The MUF from ISIRM is also compared with MUF observation from Manado-Sumedang Oblique ionosonde.